EFFECT OF USING IRON SLAG ON FOUNDRY- MOLDING MIXTURE PROPERTIES (Journal of Engineering, 2010)
This work deals with slags produced from melting processes of cast iron and steel .as an industrial solid by product with investiga effect environment in general .Huge quantities of slag are produced from foundries and steel work complexes , as (10-30)% of iron alloys produced .In order to use those quantities at the same foundries , this work investigates the using of slag in sand moulding mixtures 10,20,30 and 40 % of milled slag to the same size of silica sand , instead of silica , and prepared standard speciemens to test grean compression strength and gas permeability in green and dry cases.Results showed improvement in comp.strength in green tests, by using slag. While in dry tests, however, that comp. strength increased by using slag.But we couldn´t break dry speciemens to have given results over 10% slag because their values were over the rang of tester (6.5kg/cm²) . Accordingly we can state that slag can be used in moulding mixture at the same foundries to improve properties and to get rid from its pollution effect and transport costs.Rejects recycling is the best way to save environment -